Ultra‐Flexible µ‐ECoG Arrays Based on PEDOT:PSS Micropillars - Alice Lunghi; Michele Bianchi; Pierpaolo Greco; Riccardo Viaro; Michele Di Lauro; Luciano Fadiga; Fabio Biscarini (Advanced Materials Interfaces)
Abstract Devices capable of recording electrophysiological signals with high signal‐to‐noise ratio (SNR) and spatiotemporal resolution are crucial in neurological research. The introduction of flexible materials and conductive polymers in the fabrication of multi electrode arrays (MEAs) for electrocorticography (ECoG) enabled higher quality of recorded signals thanks to device conformability and to low‐impedance electrodes. Advances in microfabrication techniques allow a dramatic reduction in electrode size, leading to highly‐dense microelectrode arrays with increased spatial resolution. Here, the synergic contribution of surface micropatterning and of conductive polymers on the recording performance of a home‐built µECoG device is explored. The device is fabricated through a combination of conventional and unconventional micropatterning techniques, leading to an ultra‐conformable polydimethylsiloxane (PDMS) array featuring different‐size flexible micropillars forests coated with a thin layer of poly(3,4‐ethylenedioxythiophene) poly(styrenesulfonate) (PEDOT:PSS). The performance of the device is assessed in vitro by electrochemical impedance spectroscopy and in vivo by detecting somatosensory evoked potentials from the somatosensory cortex of a rat. The increasing of the geometric area has only limited effect on the recording capability in the in vivo model investigated. Nevertheless, the extremely high SNR values obtained place the proposed approach as an innovative and versatile strategy for the prototyping of ultra‐conformable µECoG devices.